Use of space and time resources by a community of lizards in the municipality of Santiago Nonualco, El Salvador (Repertorio Científico, 2022)
The coexistence of the lizards within the communities is carried out through the differential partitioning of the environmental resources. The choice and use of resources is mainly determined by the physiology of the organisms and the adjacent environmental characteristics. The objective of this study was to determine the spatial and temporal niche and the activities of a community of lizards in the municipality of Santiago Nonualco. Methods: 32 sampling points were established, and in each of these, one 100x4 m transect. Sampling was carried out between March and August 2021 using the Visual Encounter Inspection technique. The substrate, time and activity were recorded at the time each individual was observed for the first time. Only Basiliscus vittatus was present in all the microhabitats and Trunk Fallen was the most abundant substrate. In related species such as those of the Anolis genus, a strong spatial niche overlap was obtained. In most species combinations there was high temporal niche overlap, but low spatial overlap. The coexistence of this community of lizards is mainly determined by the differential use of space, which is used above all for basking.